Correlation between oral health and the quality of life of children with disabilities using healthy-dis: an observational study - Prihatiningrum, Berlian; Budirahardjo, Roedy; Probosari, Niken; Sulistiyani, Sulistiyani; Setyorini, Dyah (Universitas Padjadjaran, 2025)
Introduction: Children with disabilities require special attention due to various limitations, such as difficulty in maintaining oral hygiene, communication barriers, and behavioral challenges. This study aimed to investigate the impact of oral health on the quality of life of children with disabilities in Jember, using the Healthy-Dis software. Methods: This analytical observational study employed a cross-sectional design. The study population consisted of 180 students enrolled at SLB C TPA Jember and SLB N 1 Patrang Jember. Caries severity was assessed using the DMF-t/def-t index, oral hygiene using the OHI-S index, and oral health-related quality of life (OHRQoL) using the COHIP-SF 19 questionnaire. Dental care needs were evaluated using the Required Treatment Index (RTI). The COHIP-SF 19 and RTI instruments were modified and integrated into the Android-based Healthy-Dis application. Results: A significant correlation was found between gender, caries severity, oral hygiene status, and the quality of life of children with disabilities (p < 0.05). A strong positive correlation was observed between oral hygiene status and quality of life (r = 0.446), while caries severity and gender showed negative correlations. These findings highlight the importance of maintaining good oral hygiene to improve the overall well-being of children with disabilities. Conclusion: Oral health status—including caries severity and oral hygiene level—is significantly associated with the quality of life of children with disabilities. Efforts to promote better oral hygiene may enhance their daily functioning and overall well-being.